Peanut oleosins associated with severe peanut allergy—importance of lipophilic allergens for comprehensive allergy diagnostics - Schwager, Christian; Kull, Skadi; Behrends, Jochen; Röckendorf, Niels; Schocker, Frauke; Frey, Andreas; Homann, Arne; Becker, Wolf-Meinhard; Jappe, Uta (Journal of allergy and clinical immunology, 2017)
Peanut allergy is one of the most common and most severe food allergies in Western countries and its accurate diagnosis to prevent potential life-threatening allergic reactions is crucial. However, aqueous extracts used for routine diagnostic measurements are devoid of lipophilic allergens such as oleosins. We have recently succeeded in the isolation and purification of these unique proteins, and the present study evaluates their allergenic potential and clinical relevance. We sought to assess allergenicity and sensitization prevalence of oleosins obtained from both raw and in-shell roasted peanuts. In addition, we tested the utilization of natural and recombinant oleosins for allergy diagnostic purposes. Oleosin sensitization, prevalence, and impact of thermal processing were analyzed by immunoblot with sera from 52 peanut-allergic individuals displaying different clinical phenotypes. The application of natural and recombinant oleosins for allergy diagnostics was investigated by basophil activation test (BAT). IgE-binding epitopes were identified by oligopeptide microarray. Sensitization to oleosins was observed exclusively in peanut-allergic subjects suffering from severe systemic reactions. IgE-binding capacity of oleosins derived from in-shell roasted peanuts was increased as shown by immunoblot analysis and BAT. Both natural and recombinant molecules can be used to identify oleosin-sensitized patients by BAT. A linear epitope of Ara h 15 was determined that displays high similarity to other seed-derived oleosins. Oleosins are clinically relevant peanut allergens and most likely associated with severe allergic symptoms. In-shell roasting increases their allergenicity, which is consistent with the observation that most allergic reactions are in connection with roasted peanuts.